2009
DOI: 10.1002/jhet.175
|View full text |Cite
|
Sign up to set email alerts
|

A simple, efficient, one‐pot three‐component domino synthesis of Hantzsch pyridines under solvent‐free condition

Abstract: in Wiley InterScience (www.interscience.wiley.com).In this article, efficient and simple preparation of Hantzsch pyridine derivatives by reaction of various aldehydes and b-dicarbonyls in the presence of ammonium chlorate under solvent-free condition at 80 C is reported. The advantages of this system are the one-step procedure, high yields of the products, and the ability to carry out large-scale reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The advantages of solvent‐free procedures include cost savings, reduced energy consumption, decreased reaction times, and a considerable reduction in reactor size and, therefore, capital investment. These attributes have inspired a substantial research effort directed toward the development of solvent‐free reactions . Solid acid catalysts are interesting alternatives for the common liquid acids because of their simple handling and isolation of the reaction products and reagent .…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of solvent‐free procedures include cost savings, reduced energy consumption, decreased reaction times, and a considerable reduction in reactor size and, therefore, capital investment. These attributes have inspired a substantial research effort directed toward the development of solvent‐free reactions . Solid acid catalysts are interesting alternatives for the common liquid acids because of their simple handling and isolation of the reaction products and reagent .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the oxidative aromatization of 1,4-dihydropyridines has also been extensively studied and numerous oxidizing reagents, namely, CuBr 2 [7], SiO 2 /P 2 O 5 -SeO 2 [8], H 2 O 2 /Co(OAc) 2 [9], and Na 2 S 2 O 4 /TBHP [10], have been used for the aromatization of 1,4-dihydropyridines. Some reports have observed that the direct oxidative procedure was very efficient for the preparation of Hantzsch pyridines under microwave-assisted condition or solventfree condition [11][12][13]. However, the search for the new readily available and green methods is still being actively pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential transformations, multicomponent processes, and one‐pot procedures have become increasingly interesting because they offer simple and efficient synthetic ways to pyrroloazines .…”
Section: Introductionmentioning
confidence: 99%